Precise size control of layered double hydroxide nanoparticles through reconstruction using tripodal ligands. Issue 37 (10th August 2018) - Kuroda, Yoshiyuki; Oka, Yuya; Yasuda, Tadao; Koichi, Tatsuyuki; Muramatsu, Keisuke; Wada, Hiroaki; Shimojima, Atsushi; Kuroda, Kazuyuki
Abstract : Layered double hydroxide nanoparticles were synthesized via reconstruction, suppressing crystal growth with tripodal ligands. Abstract : Precise size control of layered double hydroxide nanoparticles (LDHNPs) is crucial for their applications in anion exchange, catalysis, and drug delivery systems. Here, we report the synthesis of LDHNPs through a reconstruction method, using tripodal ligands ( e.g., tris(hydroxymethyl)aminomethane; THAM). We found that the mechanism of reconstruction at least includes a dissolution–recrystallization process rather than topotactic transformation. THAM is immobilized on the surface of recrystallized LDHNPs with tridentate linkages, suppressing their crystal growth especially in lateral directions. The particle size of the LDHNPs is precisely controlled by the concentration of THAM regardless of the synthetic routes, such as coprecipitation and reconstruction. It is suggested that the particle size is controlled on the basis of Ostwald ripening which is governed by the equilibrium of the surface modification reaction.